माहेश्वर सूत्र और उनकी वैज्ञानिकता - Radheshyam Chaturvedi (Dr. Chinmay Pandya, 2016)
विश्व की सात्विक सत्ता अर्थात परम शिव जब आनंद से उच्छलित अथवा क्रोध से उद्रिक्त होते है तब नृत्य करते हैं। आनन्दोच्छलत्ता सृष्टि के प्रारम्भ का और क्रोधोद्रेक संहार का संकेतक होता है। सृष्टि के कर्ता ब्रह्मा के चार मानस पुत्र- सनक, सनन्दन, सनातन और सनत कुमार, परम ज्ञान की प्राप्ति के लिये तप कर रहे थे। उनकी तपस्या से प्रसन्न होकर संसार से उनका उद्धार करने के लिए भगवान् शिव ने नृत्य के अन्त में चौदह बार डमरू बजाया। इस डमरू ध्वनि से तपस्यारत सनक आदि को ज्ञान हो गया और वे मुक्त हो गये। When the eternal power of the world, i.e. the Supreme deity Lord Shiva is blissful with ecstasy or overwhelmed with anger, then he dances. Blissful thrill is an indicator of the beginning of the universe and of devastation through anger. The four Manasaputras of Brahma, the creator of the universe - Sanak, Sanandan, Sanatana and Sanat Kumar, were doing penance for the attainment of supreme knowledge. Pleased with his penance, Lord Shiva played Damru fourteen times at the end of the dance to save them from the world. This sound of damru gives wisdom to Sanak and his brothers and they get liberation.